1982
DOI: 10.1002/aic.690280421
|View full text |Cite
|
Sign up to set email alerts
|

General correlation of the initial collection efficiency of granular filter beds

Abstract: A general correlation for the prediction of the initial collection efficiency of HEMANT PENDSE and CHI TlEN granular filter beds is proposed. The correlation is based on the results obtained from trajectory calculation and the comparison between the numerical results and available experimental data. The correlation includes all the pertinent dimensionless groups and agrees with reported data within experimental accuracy.The performance of a filter can be described by its overall collection efficiency, E, defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…The tube wall is assumed to be parabolic (Payatakes et al, 1973), sinusoidal (Fedkiew and Newman, 1977) or hyperboloidal (Petersen, 1958;Venkatesan and Rajagopalan, 1980). Pendse and Tien (1982) found that trajectory calculations using a combination of all three cases mentioned above agree better with experimental data than each of the models alone. The filtration of particles is accomplished by the deposition of particles on the surface of the tube and the efficiency increases as the constriction minimum to maximum diameters ratio decreases.…”
Section: Literature Review Flow Models In Granular Bedmentioning
confidence: 62%
See 1 more Smart Citation
“…The tube wall is assumed to be parabolic (Payatakes et al, 1973), sinusoidal (Fedkiew and Newman, 1977) or hyperboloidal (Petersen, 1958;Venkatesan and Rajagopalan, 1980). Pendse and Tien (1982) found that trajectory calculations using a combination of all three cases mentioned above agree better with experimental data than each of the models alone. The filtration of particles is accomplished by the deposition of particles on the surface of the tube and the efficiency increases as the constriction minimum to maximum diameters ratio decreases.…”
Section: Literature Review Flow Models In Granular Bedmentioning
confidence: 62%
“…1979;Snaddon and Dietz, 1980;Pfeffer et al, 1981;Degani and Tardos, 1981;Pendse and Tien, 1982). For filtration of aerosol particles from gases the equation takes the form…”
Section: Introductionmentioning
confidence: 99%
“…Pendse and Tien (1982) showed that some of these earlier correlations yield results whch may differ by order of magnitude. Even among the more recent correlations, some significant differences exist.…”
Section: Comparisons With Empirical Correlationsmentioning
confidence: 99%
“…The correlation of Yoshida and Tien is a modified version of the earlier correlation proposed by Pendse and Tien (1982) and based on data reported by a number of investigators, including D'Ottavio and Goren and Thambimuthu. Furthermore, the single-collector efficiency in the Yoshda and Tien correlation was based on K, = (6/[(1 -c )~/~] ) ' /~, while for the other three correlations, 11, is based on K , = 3/2.…”
Section: Nk04"'mentioning
confidence: 99%
See 1 more Smart Citation